Twenty-Sixth Symposium on Biotechnology for Fuels and Chemicals - Davison, Brian H. (ABAB Symposium, 2005)
In Biotechnology for Fuels and Chemicals: The Twenty-Sixth Symposium, leading US and international researchers from academia, industry, and government present state-of-the-art research on how biotechnology is being used to produce high-volume, low-price products from renewable resources, as well as to improve the environment. In addition to the sessions on the conversion of lignocellulose into sugars and the conversion of sugars into products and fuels, this symposium focused on a review of the concept of the biorefinery-the integrated production of multiple products and energy at one site. Session topics included advanced feedstock production and processing, enzyme and microbial biocatalysts, bioprocess research and development, opportunities in biorefineries, and commercialization of biobased products. There was also a session on improving the rate, concentration, and efficiency of biological hydrogen production, and on designing processes to accomplish this. There was a general recognition among the participants of the need to move beyond corn sugar as the primary feedstock into lignocellulosics. Cutting-edge and authoritative, Biotechnology for Fuels and Chemicals: The Twenty-Sixth Symposium provides an excellent overview of current research and development in the production of commodity fuels and chemicals via biological transformation.